Carcinoid tumor in carina secondary - Fernandes Pereira, André Venâncio (2008)
Carcinoid tumor is a serotonin-producing malignant tumor belonging to a class of neoplasms known as the neuroendocrine tumors. Carcinoid tumors of the lung are much less common and represent 1% to 2% of all lung cancers. The current classification of lung tumors recognizes bronchial typical carcinoid as low-grade neuroendocrine tumors. Symptoms are usually related to local compression and obstruction of the bronchial tree. Preoperative diagnosis is usually obtained without bronchoscopic biopsy. The authors report the case of a woman with typical carcinoid tumor in the left lower lobar bronchus, next to the secondary carina. It was treated with bronchoplastic resection, and associated to lymphadenectomy. The complete surgical resection remains the only therapy with curative intent in the majority of patients. Local relapse can be treated successfully with surgery, whereas distant metastases have a poor prognosis even after chemotherapy.